Delayed cell death in human and fish skin cell lines after exposure to UVA and UVB - O'Reilly, Joseph Patrick (Trinity College (Dublin, Ireland). School of Biochemistry and Immunology, 2000)
The effects of ultraviolet radiation on humans and animals are receiving increasing attention and much interest has recently been focused on the environmental effects of UVA and UVB. This study compares the effects of UVA and UVB on two human cell lines, HaCaT and HaCaT-ras, and two fish cell lines, CHSE and EPC.
Keywords: Biochemistry, Ph.D; Ph.D. Trinity College Dublin